CHARACTERISTICS OF COMORBIDITIES IN ADULT PATIENTS WITH SEBORRHEIC DERMATITIS AT THE NATIONAL HOSPITAL OF DERMATOLOGY AND VENEREOLOGY (Vietnam Journal of Community Medicine, 2026)
Objectives: To investigate comorbidity characteristics among adult patients with seborrheic dermatitis at the National Hospital of Dermatology and Venereology.Subjects: 263 adult patients diagnosed with seborrheic dermatitis at the National Hospital of Dermatology and Venereology during the period from November 2025 to April 2026.Methods: This study utilized a prospective, cross-sectional descriptive design.Results: Patients in the 20-39 age group accounted for 60.5% of the study population, with a higher prevalence in males compared to females (64.6% vs 35.4%). The most frequent sites of involvement were the scalp (83.3%), followed by the nasolabial folds (63.9%) and the eyebrows (23.2%). Regarding disease severity, 70.8% of the patients presented with moderate symptoms.Dermatological comorbidities: acne, atopic dermatitis, and alopecia were the most frequent dermatological comorbidities, accounting for 14.8%, 8.7%, and 5.3%, respectively. No significant correlation was found between dermatological comorbidities and disease severity. Stress and dyslipidemia were the most common systemic comorbidities, at 20.9% and 15.6%, respectively. There was a significant correlation between systemic comorbidities and disease severity (p < 0.05). Psychological stress was significantly associated with pruritus intensity (OR = 1.2; p < 0.001) and overall disease severity (OR = 1.7; p = 0.005). Similarly, dyslipidemia showed a strong correlation with the degree of erythema (OR = 2.2; p < 0.001), desquamation (OR = 1.3; p = 0.018), and disease severity (OR = 1.1; p < 0.001).Conclusions: Atopic dermatitis, acne, and alopecia are the most common dermatological comorbidities, no correlate with the severity of seborrheic dermatitis. Stress and dyslipidemia are the most frequent systemic comorbidities and are closely linked to disease severity. Stress is associated with more severe pruritus, while dyslipidemia is associated with more severe erythema and scaling.
Keywords: Comorbidities, seborrheic dermatitis.